2005
DOI: 10.1111/j.1365-3040.2005.01392.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf internal diffusion conductance limits photosynthesis more strongly in older leaves of Mediterranean evergreen broad‐leaved species

Abstract: Leaf age-dependent changes in structure, nitrogen content, internal mesophyll diffusion conductance ( g m ), the capacity for photosynthetic electron transport ( J max ) and the maximum carboxylase activity of Rubisco ( V cmax ) were investigated in mature non-senescent leaves of Laurus nobilis L., Olea europea L. and Quercus ilex L. to test the hypothesis that the relative significance of biochemical and diffusion limitations of photosynthesis changes with leaf age. The leaf life-span was up to 3 years in L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
265
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(306 citation statements)
references
References 61 publications
26
265
3
3
Order By: Relevance
“…Increasing needle tissue density has lowered CO 2 concentration in intercellular spaces and probably increases mesophyll resistance to CO 2 that leads to a reduction of PNUE with A. alba needle age (Niinemets et al 2005(Niinemets et al , 2006. The other authors showed that mesophyll (internal) conductance to CO 2 (g i ) was correlated with the surface area of chloroplasts exposed to intercellular air space and g i decreased with leaf age which might also be expected in our study tree (Hanba et al 2001;Miyazawa and Terashima 2001).…”
Section: Discussionsupporting
confidence: 64%
“…Increasing needle tissue density has lowered CO 2 concentration in intercellular spaces and probably increases mesophyll resistance to CO 2 that leads to a reduction of PNUE with A. alba needle age (Niinemets et al 2005(Niinemets et al , 2006. The other authors showed that mesophyll (internal) conductance to CO 2 (g i ) was correlated with the surface area of chloroplasts exposed to intercellular air space and g i decreased with leaf age which might also be expected in our study tree (Hanba et al 2001;Miyazawa and Terashima 2001).…”
Section: Discussionsupporting
confidence: 64%
“…While limited stomatal conductance is widely recognized to limit photosynthetic rate, Niinemets et al (2011) reviewed the effects of mesophyll conductance in plants and highlighted the limited internal diffusion conductance of sclerophyllous plants, including conifers, as providing a constraint to photosynthetic rate that can be as large as that due to stomatal conductance. Reduced mesophyll conductance in sclerophyllous plants is in turn attributable to greater investment in support tissue, particularly thicker cell walls, associated with greater leaf longevity (Niinemets et al, 2005). Low mesophyll conductance has been observed in the New Zealand podocarp Dacrydium cupressinum, to the extent that the diffusive constraint on photosynthesis imposed by mesophyll exceeded that imposed by stomata (DeLucia et al, 2003).…”
Section: Photosynthetic and Growth Responses To Variation In C Amentioning
confidence: 99%
“…Technical advances in the measurement of gas exchange and fluorescence, and isotopic techniques, have provided more-accurate means to assess successive resistances across the entire CO 2 diffusion pathway through the leaf, prompting their importance for carbon uptake to be reconsidered Ennahli and Earl, 2005;Warren, 2006). In this context, it is important to elucidate the changes in biochemical factors and diffusion resistances during photosynthesis when plants are submitted to naturally stressful conditions, such as drought (Niinemets et al, 2005;Galmés et al, 2007;Flexas et al, 2009). This dual limitation influences the potential of seedlings to maintain a positive leaf carbon balance, and should be accounted for when assessing the ultimate consequences of water stress on ecological succession and niche partitioning under sub-Mediterranean environments (Kunstler et al, 2005;Robson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%